Sixth Five Year Plan 1980-85 Annual Plan 1981-82 Part I - Planning Commission (Planning Commission, 1980)
Government of India decided to shelve the 1978-83 plan (April, 1980) and the newly constituted National Development Council (NDC) took up the work of spelling out objectives and preparation of the frame-work of the 1980-85 Sixth Plan. 2. Accordingly, the reconstituted Planning Commission prepared Draft Guidelines for consideration of the NDC and circulated them to all the State Governments (May 1980). The NDC, in its meeting (August 1980) approved both the main objective as well as the frame-work of the Sixth Plan and the States were advised to work out detailed proposals within those parameters for consideration by the Planning Commission. Accordingly, the Maharashtra Draft Sixth Five Year Plan was discussed with the Deputy Chairman of the Planning Commission by the Chief Minister in December. 1980, and the Plan as emerged out of this discussion (Rs. 6,175 crores for the Plan period, and Rs. 1,080 crores for the 1981-82 Annual Plan ) was incorporated in the final Draft Document of the Country’s Sixth Plan which was duly considered and approved by the NDC on 13th and 14th of February, 1981.
Planning Department Government of Maharashtra